Rice productivity variations in Kemubu Agricultural Development Authority (KADA) as affected by pests and diseases / Shafinie Safin Amran (Faculty of Plantation and Agrotechnology, 2016)
Rice,Oryza sativa production has always been impacted with many biotic and abiotic factors such as soil fertility, climate change, irrigation system and pests and diseases. Kemubu Agricultural Development Authority (KADA) which is located in Kelantan is the second largest rice granary in Malaysia after Muda Agricultural Development Authority (MADA) Kedah, was used as a case study area. The objectives of this study were to analyse Kada's rice productivity in relation to pests and diseases in both seasons within the last 5 years (2010-2014). The Secondary data on the Census of Rice Damage (Pest, diseases and weed) obtained from the Department of Agriculture, Kota Bharu, and the yield data from KADA were used in this case study. All the data were tabulated and sorted using Microsoft Excel, and descriptive statistics and graphic were carryout using Statistical Analysis Software (SAS) and Sigma Plot l1.0 respectively. The results revealed that there were great variations of pests and diseases incidence in KADA's rice farm with respect to type of pest and disease incidence , localities (districts) and time (years).